Evaluation of Shopee Live Feature Usability among Millennial Consumers using the System Usability Scale - Laylin Permadani; Evi Maria (Universitas Islam Indragiri, 2026)
Digital transformation has driven e-commerce toward real-time interaction through live commerce, increasing user engagement while also introducing greater usage complexity. This study aims to evaluate the usability of the Shopee Live feature among millennial consumers. A quantitative approach was employed using the System Usability Scale (SUS) instrument. Data were collected from 100 respondents through purposive sampling and analyzed descriptively along with reliability testing. The results indicate an average SUS score of 66.55, which falls within the Marginal-High category, suggesting that the Shopee Live feature is generally acceptable but has not yet reached an optimal level of usability. Although ease of use, functional integration, and learnability were evaluated positively, users still experienced challenges related to system complexity, consistency, and usage effort. In the context of live commerce, usability is determined not only by ease of use but also by the stability of interaction under real-time conditions. Cognitive load resulting from multitasking demands was identified as a key mechanism affecting usage efficiency. These findings highlight the importance of integrating real-time interaction and cognitive load considerations into usability evaluation, while also providing practical implications for the development of more adaptive live commerce features.